Correlation of Lipopolysaccharide Endotoxin Level in Cotton Dust with the Increase of TNFα Level and the Decline of Lung Function in Cotton Spinning Factory Workers - Fadilatus Sukma Ika Noviarmi; Leli Indahwati; Soedjajadi Keman (Makara Journal of Health Research, 2014)
Lipopolysaccharide (LPS) endotoxin contained in cotton dust may cause airway inflammation and decline of lung function when inhaled, which eventually leads to respiratory symptoms. The objective of this research is to analyze the correlation of the exposure of LPS endotoxin in cotton dust with the increase of TNFα level and the decline of lung function after one day's work. This study applies analytical observation method and prospective cohort approach. Main participants of this study were the workers of a cotton spinning factory located in Tulangan District, Sidoarjo Regency, East Java Province. Sixteen samples from cotton factory were taken as study group, and twenty three samples from village administrators were taken as control group. Data collection involves several techniques: spirometry, laboratory test, and interview. Results showed that concentration of personal dust has a significant relationship with the decline of FVC, %FVC, FEV1, and %FEV1, with Pearson correlation test showing p<0.05. LPS endotoxin in personal dust samples has a significant relationship with the increase of blood serum TNFα and the decline of FEV1 and %FEV1, with Pearson correlation test showing p>0.05. The research concludes that the level of LPS endotoxin was strongly related to the increase of blood serum TNFα and the decline of lung function. Development of more effective preventive measures such as stronger enforcement of worker's health maintenance regulations and use of personal protective equipment is needed to ensure the best protection of cotton workers' health.